IDENTIFICATION OF THERMOPHILIC BACTERIA FROM THE HOT SPRING OF KAZAKHSTAN AND ASSESSMENT OF THEIR ENZYMATIC ACTIVITY (Experimental biology, 2023)
Thermophilic microorganisms are a less studied, but important group of microorganisms due to their ability to produce enzymes that are unique in their properties. In this regard, it is required to study previously unexplored thermal springs on the territory of Kazakhstan in order to search for new thermophilic microorganisms with biotechnological potential. For this purpose, under this study, for the first time, thermophilic bacteria from a geothermal source near the city of Zharkent, Almaty region, Republic of Kazakhstan were isolated and characterized for their ability to produce extracellular hydrolytic enzymes (amylase, cellulase, protease, and lipase). Based on the results of the studies, it was determined that three of the five isolates showed high enzymatic activity for all four types of enzymes and the rest produced at least several extracellular hydrolytic enzymes. Phylogenetic analysis for the universal bacterial 16s rRNA gene and biochemical characterization results (on API 50CHE and API Zym strips) showed that all derived isolates from the thermal spring differ from the currently known species of the genus Geobacillus, which indicates that this geothermal spring is a rich habitat for new unexplored species of microorganisms with unique enzymes. Moreover, one of the five isolates showed the highest optimal growth temperature at 75°C among the representatives of this genus.
Keywords: thermophilic bacteria, identification, 16S rRNA, phylogenetic analysis, hydrolytic enzymes